Answer:
f=100
Step-by-step explanation:
Answer:
y = 47
Step-by-step explanation:
y = 2x + 3
y = 2(22) + 3
y = 47
Well the answer i got was

when i multiplied
the answer i got when i added was
Answer:
Step-by-step explanation:
27,33
9*3 is 27
11*3 is 33
33-27 is 6
i only have one, sorry!
The equation of the parabolas given will be found as follows:
a] general form of the parabolas is:
y=k(ax^2+bx+c)
taking to points form the first graph say (2,-2) (3,2), thus
y=k(x-2)(x-3)
y=k(x^2-5x+6)
taking another point (-1,5)
5=k((-1)^2-5(-1)+6)
5=k(1+5+6)
5=12k
k=5/12
thus the equation will be:
y=5/12(x^2-5x+6)
b] Using the vertex form of the quadratic equations:
y=a(x-h)^2+k
where (h,k) is the vertex
from the graph, the vertex is hence: (-2,1)
thus the equation will be:
y=a(x+2)^2+1
taking the point say (0,3) and solving for a
3=a(0+2)^2+1
3=4a+1
a=1/2
hence the equation will be:
y=1/2(x+2)^2+1